Tingkat Kesejahteraan Nelayan di Desa Kusamba, Kecamatan Dawan, Kabupaten Klungkung - NI LUH PUTU MEILINA KUSUMA DEWI; MADE ANTARA; I DEWA GEDE RAKA SARJANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Welfare Level of Fishermen in Kusamba Village, Dawan District, Klungkung Regency. Seeing the low level of welfare caused by the low income of fishermen and still open opportunities to increase marine fishery production in Kusamba Village. The method of analysis is quantitative and qualitative. Data collection was done by interview, observation, documentation and literature study methods. Respondents amounted to 31 people taken from three groups of fishermen. The variables in this study are income and the level of welfare with the indicators used are income, expenditure and consumption patterns, health, education, employment and housing. The result of this research is the cash cost of capture fisheries business is Rp 39.382.788.39/year and the total income is Rp 38.465.578.71/year or Rp 3.205.464.89/month. The results for the welfare level of capture fisheries fishermen are in the moderately prosperous category with a score of 2,346. Based on the results of the study, it is recommended to increase the role of the government in terms of empowerment, providing facilities to the community in the form of agribusiness development facilities such as market information, increasing market access, capital and developing partnerships with other business institutions.